2010
DOI: 10.1097/gme.0b013e3181b48a88
|View full text |Cite
|
Sign up to set email alerts
|

Is antral follicle count a genetic trait?

Abstract: Maternal age of menopause predicts antral follicle count and its decline, indicating a genetic component to this trait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
0
13
1
1
Order By: Relevance
“…As in previous studies, there is considerable variation in AFC in the population, and age alone only modestly explained the decline in AFC (R 2 ¼ 0.37). The study revealed that the median decline of AFC in normally menstruating women was 2.4% per year, or 0.4 follicles per year, which is lower than values reported in previous studies that found a decrease of 0.95, or 0.97 follicles per year (14,19), or 8.2 % per year (15). Conversely, Ng et al (18) investigated the AFC in a fertile population of 119 women and found a decline of AFC at 0.35 follicles per year, which is similar to results of the present study.…”
Section: Figurecontrasting
confidence: 55%
See 3 more Smart Citations
“…As in previous studies, there is considerable variation in AFC in the population, and age alone only modestly explained the decline in AFC (R 2 ¼ 0.37). The study revealed that the median decline of AFC in normally menstruating women was 2.4% per year, or 0.4 follicles per year, which is lower than values reported in previous studies that found a decrease of 0.95, or 0.97 follicles per year (14,19), or 8.2 % per year (15). Conversely, Ng et al (18) investigated the AFC in a fertile population of 119 women and found a decline of AFC at 0.35 follicles per year, which is similar to results of the present study.…”
Section: Figurecontrasting
confidence: 55%
“…The majority of studies have investigated AFC in infertile patients (19,27,28) or patients with proven fertility (15,16,18,29). Only two studies have been performed on the general population; however, one was limited to a small number of subjects (n ¼ 31) (14).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…La gran mayoría de los estudios se han enfocado en investigar el recuento de folículos antrales en pacientes infértiles 2,10,11 . En este estudio evaluamos la reserva ovárica de mujeres en edad reproductiva y con fertilidad probada en población chilena, lo que marca una importante diferencia con otros estudios, y nuestros resultados confirman que existe un declive en el RFA relacionado con la edad, que disminuye en forma constante durante todo el período reproductivo 12,13 .…”
Section: Discussionunclassified